O olho do poder: um estudo sobre as relações de poder nas práticas laborais de uma Secretaria Municipal de Educação - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research aims to analyze how power relations are manifested in the workpractices of the Department of Education of the municipal network of Santana do Livramento. For this purpose, the qualitative approach was uses as a research methodology, with an exploratory nature based on the genealogical method. The data were obtained through the three collection techniques: semi-structured interview, with 9 servers, including 7 effective and 2 commissioned, no participant observation of the activities and routines of the folder and documental research carried out through the analysis of news and reports in newspaper, being later verified through enunciative analysis. The results revealed the presence of the different types of power in the work practices of the branch, with Pastoral, Charismatic, One- Dimensional, Two-Dimensional, Three-Dimensional and Sovereign powers being evidenced through the perception of these servants in terms of characteristics and forms to manage the administrations that were at the head of the Secretary. In consonance with this, these speeches made it possible to visualize the great influence of politics in the conduct of activities, directly interfering both in power relations and in the progress of all processes competent to the folder. With regard to the configuration of the power diagram there were evidences of statements of Security and Conformism, Cronyism, Self Indulgence and Collegiality, glimpsing the historical understanding of the reasons that lead servers to perform certain practices, the way in which power it is inserted and interferes in the relationships and also in the day to day labor of the employees working in the town’s Education Department.
The eye of power: a study on power relations in the practices in the work practices of a Municipal Department of Education
El ojo del poder: um estudio sobre las relaciones de poder en las prácticas de trabajo de una Secretaria Municipal de Educación
Keywords: Relações de poder; Servidores; Práticas laborais; Influência política; Power relations; Servers; Work practices; Political influence; Relaciones de poder; Practicas de trabajo; influencia politica; CNPQ::CIENCIAS SOCIAIS APLICADAS